The Impact of Amorphisation and Spheronization Techniques on the Improved in Vitro & in Vivo Performance of Glimepiride Tablets - Rana Refaat Makar; Randa Latif; Ehab Ahmed Hosni; Omaima Naim El Gazayerly (Tabriz University of Medical Sciences, 2017)
Purpose: Triple solid dispersion adsorbates (TSDads) and spherical agglomerates (SA) present new techniques that extensively enhance dissolution of poorly soluble drugs. The aim of the present study is to hasten the onset of hypoglycemic effect of glimepiride through enhancing its rate of release from tablet formulation prepared from either technique. Methods: Drug release from TSDads or SA tablets with different added excipients was explored. Scanning electron microscopy (SEM) and effect of compression on dissolution were illustrated. Pharmacodynamic evaluation was performed on optimized tablets. Results: TSDads & SA tablets with Cross Povidone showed least disintegration times of 1.48 and 0.5 min. respectively. Kinetics of drug release recorded least half-lives (54.13 and 59.83min for both techniques respectively). Cross section in tablets displayed an organized interconnected matrix under SEM, accounting for the rapid access of dissolution media to the tablet core. Components of tablets filled into capsules showed a similar release profile to that of tablets after compression as indicated by similarity factor. The onset time of maximum reduction in blood glucose in male albino rabbits was hastened to 2h instead of 3h for commercial tablets. Conclusion: After optimization of tablet excipients that interacted differently with respect to their effect on drug release, we could conclude that both amorphisation and spheronization were equally successful in promoting in vitro dissolution enhancement as well as providing a more rapid onset time for drug action in vivo.